Investigation of a hysteretic shear-flexure hinge model for reinforced concrete elements - Longalong, Romeo Eliezer U. (College of Engineering, University of the Philippines Diliman, 2015)
In order to prevent the collapse of structures, seismic analysis can be used to understand and improve the response of a structure subjected to earthquake loadings. A recent trend in structural seismic assessment involves the use of nonlinear dynamic analysis which subjects a numerical model to ground motion even up to collapse. This analysis requires a hinge model that captures materi al behavior up to fa ilure. In this study, a nonlinear hinge model that can simulate biaxial bending behavior and shear behavior is developed for reinforced concrete beams and columns. The hinge model is composed of axial springs that act as fibers of concrete and steel, and shear springs in the transverse directions. These springs incorporate the associated nonlinear hysteretic material behavior. Reinforced concrete elements were modeled as assemblies of rigid body components connected by the proposed hinge model. The nonlinear hinge was validated by comparing the force-displacement responses of the reinforced concrete columns with experimental pseudo-dynamic tests. A total of 16 experimental results, obtained from the PEER Structural Perfonnance Database, were chosen to represent the different failure modes of rectangul ar and circul ar columns. The comparisons show that the proposed hinge model can describe the pushover and cyclic response of flexurecritical elements.